Central nervous system involvement in late‐onset Pompe disease: clues from neuroimaging and neuropsychological analysis. (15th November 2018) - Musumeci, O.; Marino, S.; Granata, F.; Morabito, R.; Bonanno, L.; Brizzi, T.; Lo Buono, V.; Corallo, F.; Longo, M.; Toscano, A.
Abstract : Background and purpose: Late‐onset Pompe disease (LOPD) is a rare, multisystem disorder that is well established to mainly impair skeletal muscle function. Systematic studies exploring brain functions in LOPD are lacking. The aim of this study was to detect morphological and functional brain alterations as well as neuropsychological impairment in LOPD. Methods: We studied 21 patients (10 male, mean age 49 ± 18.4 years) with defined diagnosis of LOPD, divided into two groups: one with pre‐symptomatic hyperCKemia with no muscle weakness and the second with limb‐girdle muscle weakness. All patients underwent 3T magnetic resonance imaging (MRI) to obtain morphological/angiographic evaluation as well as normalized cortical brain volume and resting‐state functional MRI. Fazekas score was applied to quantify white matter lesions, whereas Smoker's criteria were used to examine dolichoectasia. A complete neuropsychological assessment was performed. Results: The MRI data showed that 12/21 patients (57%) demonstrated signs of cerebral vasculopathy, with a Fazekas score >2 in 67%. According to Smoker's criteria, 11/21 patients (52%) had a dolichoectasia of the vertebrobasilar system; an intracranial aneurysm was detected in 3/21 patients (14%). Resting‐state functional MRI demonstrated significantly decreased brain connectivity in the salience network with a more relevant reduction in the bilateral middle and superior frontal gyrus. Gray matter atrophy correlated with age and disease duration. A mild impairment in executive functions was also identified. Conclusions: In this LOPD cohort the results showed morphological and functional brain alterations with mild neuropsychological dysfunction, mainly in the limb‐girdle muscle weakness group. Cerebrovascular alterations seemed to be not related to common risk factors, suggesting a major role of enzymatic deficiency in the pathogenesis of brain abnormalities.